Efektivitas Pemanfaatan Kawasan Wisata Air Terjun Tujuh Tingkat Batangkoban Sebagai Pendapatan Asli Daerah Kabupaten Kuantan Singingi - GUSTRI JASDI; TUTI KHAIRANI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Effective Use Of The Tourist Area Of Seven Waterfalls Batangkoban Level As The District of Hulu Kuantan Kuantan District Local Revenue Singingi. Waterfall tourist area batangkoban seven levels has the potential to be developed in order to improve the regional economy or the economy of communities around the area . However, to exploit the tourist areas are not going well and also tourist areas have not been able to contribute in improving the regional economy. The purpose of this research is to examine the effectiveness of the utilization of the tourist area of seven waterfalls batangkoban level as local revenue and the factors that hinder the effective use of the tourist area . This study used qualitative research methods to the discussion of the fact that there is a description field. The results of this research note that the effectiveness of the utilization of the tourist area was not effective and was not fit for purpose or planning to be achieved . Factors that influence the effectiveness of the utilization of the tourist areas including goal achievement strategy that does not go according to , lack of appropriate policy , planning was not effective , the implementation of the programs, facilities and quality infrastructures poor and weak monitoring and control system is done to the areas tour